Analisis Kemandirian Belajar Mahasiswa dalam Pembelajaran Online di Masa Pendemi Covid-19 - Ratna Widyaningrum; Ema Butsi Prihastari; Ifa Hanifa Rahman (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This study aims to determine: 1) student learning independence in online learning, 2) learning models that can be used to foster student learning independence in science learning, 3) appropriate learning resources in fostering student learning independence. The research was conducted on the 6th semester students of the Elementary School Teacher Education Study Program, FKIP UNISRI, totaling 29 students. The research method used is descriptive qualitative as an initial needs analysis in designing appropriate learning to foster student learning independence during distance learning. The sampling technique was carried out by purposive sampling. Data collection techniques are observation, interviews, questionnaires, and documentation. Based on the results of data analysis, it was found that 1) The average score of the student learning independence questionnaire was 83.3 where 17.24% was in the good category and 82.76% in the sufficient category. So it can be concluded that student learning independence is not optimal. 2) The appropriate learning model is project-based learning. 3) Learning resources used by students in fostering independent learning include lecture modules, scientific journals, videos, youtube, books, and the surrounding environment